PERTUMBUHAN EKONOMI KREATIF BERBASIS KERAJINAN ROTAN (STUDI KASUS ALEXANDER BORNEO PALANGKA RAYA) - Agustini, Mega; Edwin, Immanuel; Sundari, Sundari (STKIP Persada Khatulistiwa Sintang, 2025)
The increase in sales or revenue has a significant impact on economic growth, with creativity being the main driver to achieve it. One approach to fostering economic growth is through the creative economy, which can be leveraged by MSMEs in Central Kalimantan, an area rich in rattan potential. This study aims to identify the supporting and inhibiting factors in the development of the rattan craft industry, as well as explore its impacts on the surrounding community, including job creation, income generation, and the preservation of local culture. A qualitative approach with a case study method was employed. The research was conducted at Alexander Borneo, Palangka Raya, Central Kalimantan, with Mrs. Corry as the primary informant. The findings reveal that efficient distribution and extensive promotion are key factors driving economic growth. On the other hand, the main challenges faced by Alexander Borneo include fluctuations in production and the limitations of suppliers, who are not always able to meet market demand. This study provides insights into the importance of managing distribution and suppliers to ensure smooth MSME operations, as well as recommendations for enhancing business resilience through supplier diversification and improved production efficiency